EVALUATION OF EDUCATION IMPLEMENTATION OF LINK AND MATCH SYSTEMS OF THE INDUSTRIAL AND VOCATIONAL SCHOOL IN YOGYAKARTA PROVINCE - Arif Bintoro Johan; Slamet PH; Widodo Widodo (Universitas Sarjanawiyata Tamansiswa, 2019)
This study aims to evaluate the implementation of schools and industries in the implementation of dual system education (PSG) that is in line with the needs of the workforce. This research is a quantitative evaluation that is descriptive. The evaluation stage uses the Context, Input, Process, and Product (CIPP) models. A qualitative approach is used for the PSG development strategy. This research consists of three stages: the planning stage, the evaluation stage, and the strategy development stage. The planning stage consists of diagnosing problems, planning instruments. The second stage, conducting the evaluation, data analysis and presentation of the evaluation results to the main stakeholders through a group discussion forum. The third stage is through a review by the promoter / expert for validating research products. Data collection through questionnaires, in-depth interviews, field observations, and documentation, using questionnaires, interview sheets, documents, rating scale observation sheets and anecdotal notes. The population taken was the industry and vocational groups of the Automotive and Machining Engineering group in DIY Province with a total sample of five industries, 210 vocational students, 14 productive teachers, and 14 industry leaders. The results of the study were analyzed qualitatively and quantitatively. The results showed that, first, the results of the implementation of dual system education in terms of: (1) Context of the policies and objectives of the PSG program received an average score of 4.32 (very high); (2) Facilities and infrastructure inputs get an average score of 4.15 (high), financing gets an average score of 4.31 (very high), the supervisors get an average score of 4.38 (very high); (3) The process of implementing PSG gets an average score of 4.00 (high), the constraints factors of PSG get an average score of 4.05 (high), the assessment of the implementation of PSG gets an average score of 4.03 (high); (4) Product in terms of quality of vocational school students get an average score of 4.35 (very high), in terms of the benefits of PSG get a score of 4.23 (high).